2002
DOI: 10.1590/s0034-72992002000500005
|View full text |Cite
|
Sign up to set email alerts
|

Candidíase oral como marcador de prognóstico em pacientes portadores do HIV

Abstract: Introdução: A candidíase oral é uma das doenças oportunistas mais fortemente associadas à infecção pelo Vírus da Imunodeficiência Humana (HIV). Vários relatos epidemiológicos enfatizam a prevalência da candidíase em pacientes HIV positivos e ressaltam a sua importância como marcador da progressão da doença e preditivo para o aumento da imunodepressão. Objetivo: Verificar as alterações estomatológicas em pacientes portadores do HIV tratados no Hospital Heliópolis - São Paulo, Brasil e comparar com a literatura.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
37

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 19 publications
0
12
0
37
Order By: Relevance
“…HIV infected patients often develop oropharyngeal candidiasis, while candidemia has been cited as the fourth most frequent bloodstream infection in patients at intensive care units (ICUs) in the USA 5,13,28 .…”
Section: Introductionmentioning
confidence: 99%
“…HIV infected patients often develop oropharyngeal candidiasis, while candidemia has been cited as the fourth most frequent bloodstream infection in patients at intensive care units (ICUs) in the USA 5,13,28 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving 200 patients in a hospital in Ribeirão Preto, in the State of São Paulo, Brazil, a rate of 59% male patients was determined 10 , while Cavassani et al 11 found 69.1%; however, in the current phase of the disease, an increased incidence of infection among women is occurring 12 .…”
Section: Discussionmentioning
confidence: 97%
“…In a study involving 1,837 patients in the City of São Paulo, Gabriel et al 17 verified the highest percentage (46.8%) of infected individuals in the age range of 30 to 39 years old, while Cavassan et al 11 reported the highest percentage (47.1%) in the age range of 31 to 40 years old. Gir et al 10 determined a median age of 38.2 years old, while it was 36 years old in the study of Lewden 18 .…”
Section: Discussionmentioning
confidence: 97%
“…The frequency of oral candidiasis in HIV-positive patients varies among different studies, but the condition may affect up to 94% of infected individuals depending on the stage of infection and the population studied (3,29). Candidiasis is a reliable marker of HIV disease progression (11).…”
Section: Discussionmentioning
confidence: 99%
“…Greenspan (6) reported that 41% of patients with AIDS had candidiasis during the initial stage of the disease. According to Cavassani et al (3), candidiasis and hairy leukoplakia were among the most frequent diseases observed in HIV-seropositive patients with a CD4+ count of less than 200 cells/mm 3 . In the present study, no intraoral lesions were observed in 86.7% of the patients with HIV.…”
Section: Discussionmentioning
confidence: 99%